Left ventricular functional, structural and energetic effects of normal aging: Comparison with hypertension. - Jehill D Parikh; Kieren G Hollingsworth; Dorothy Wallace; Andrew M Blamire; Guy A MacGowan (PLoS ONE)
Objectives Both aging and hypertension are significant risk factors for heart failure in the elderly. The purpose of this study was to determine how aging, with and without hypertension, affects left ventricular function. Methods Cross-sectional study of magnetic resonance imaging and 31P spectroscopy-based measurements of left ventricular structure, global function, strains, pulse wave velocity, high energy phosphate metabolism in 48 normal subjects and 40 treated hypertensive patients (though no other cardiovascular disease or diabetes) stratified into 3 age deciles from 50-79 years. Results Normal aging was associated with significant increases in systolic blood pressure, vascular stiffness, torsion, and impaired diastolic function (all P<0.05). Age-matched hypertension exacerbated the effects of aging on systolic pressure, and diastolic function. Hypertension alone, and not aging, was associated with increased left ventricular mass index, reduced energetic reserve, reduced longitudinal shortening and increased endocardial circumferential shortening (all P<0.05). Multiple linear regression analysis showed that these unique hypertensive features were significantly related to systolic blood pressure (P<0.05). Conclusions 1) Hypertension adds to the age-related changes in systolic blood pressure and diastolic function; 2) hypertension is uniquely associated with changes in several aspects of left ventricular structure, function, systolic strains, and energetics; and 3) these uniquely hypertensive-associated parameters are related to the level of systolic blood pressure and so are potentially modifiable.